2015
DOI: 10.7589/2013-07-157
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Bacterial Microbiota Isolated from the Cloaca of the European Pond Turtle (Emys orbicularis) in Poland

Abstract: We conducted a comparative analysis of the aerobic cloacal bacteria of European pond turtles (Emys orbicularis) living in their natural environment and juvenile turtles reared under controlled conditions in a breeding center. We included 130 turtles in the study. The aerobic bacteria isolated from the cloaca of the juvenile turtles were less diverse and more prevalent than the bacteria isolated from free-living adults. We isolated 17 bacterial species from juvenile captive turtles, among which the dominant spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 10 publications
2
26
2
Order By: Relevance
“…There was no correlation observed between the turtles and seawater bacteria composition, so it was suggested that Proteus bacteria should be treated as the physiological microflora of green turtles [127]. P. mirabilis was also commonly found as inhabiting the cloaca of European pond turtles ( Emys orbicularis ), especially captive ones, from Poland [102]. P. vulgaris was the predominant species, and some P. mirabilis strains were also identified in cloacal and oral swabs of loggerhead sea turtles ( Caretta caretta ) inhabiting the Sicilian Channel, the South Tyrrhenian Sea, and the Ionian Sea [42].…”
Section: Proteus Spp In Animals—adverse and Friendlymentioning
confidence: 99%
“…There was no correlation observed between the turtles and seawater bacteria composition, so it was suggested that Proteus bacteria should be treated as the physiological microflora of green turtles [127]. P. mirabilis was also commonly found as inhabiting the cloaca of European pond turtles ( Emys orbicularis ), especially captive ones, from Poland [102]. P. vulgaris was the predominant species, and some P. mirabilis strains were also identified in cloacal and oral swabs of loggerhead sea turtles ( Caretta caretta ) inhabiting the Sicilian Channel, the South Tyrrhenian Sea, and the Ionian Sea [42].…”
Section: Proteus Spp In Animals—adverse and Friendlymentioning
confidence: 99%
“…The presence of Y. ruckeri was also observed in reptiles. Nowakiewicz et al (2015), carried out a study where the cloaca flora of 130 mud turtles was tested. Yersinia ruckeri was isolated in two of the specimens (Nowakiewicz et al, 2015).…”
Section: B Irds Rep Tile S and Mammal Smentioning
confidence: 99%
“…This species has a high risk of extinction, and it is under legal protection and covered under the Natura 2000 project (Nowakiewicz et al 2015). In Lithuania, the European pond turtle has been under legal protection since 1976 and is listed as an endangered species in the Lithuanian Red Book.…”
Section: Introductionmentioning
confidence: 99%
“…These are frequent -particularly in individuals kept in breeding centers (Glazebrook andCampbell 1990, Oros et al 2005). Although water-dwelling species might have intrinsic immunity against various pathogens, turtles are carriers of different bacterial species including pathogenic ones (Nowakiewicz et al 2015). The most prevalent bacterial species found in free-living European pond turtles in neighboring Poland were Enterococcus faecalis, Escherichia coli and Staphylococcus spp., i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation